2021
DOI: 10.3390/ijms22189674
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Metabolites from Antarctic Fungal Strain Pleosporales sp. SF-7343 in HaCaT Human Keratinocytes

Abstract: Chemical investigation of the Antarctic fungi Pleosporales sp. SF-7343 revealed four known secondary fungal metabolites: alternate C (1), altenusin (2), alternariol (3), and altenuene (4). The compound structures were identified primarily by NMR and MS analyses. Atopic dermatitis, an inflammatory disease, is driven by the abnormal activation of T helper (Th) 2 cells and barrier dysfunction. We attempted to identify the anti-inflammatory components of SF-7343. Initial screening showed that compounds 1 and 3 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A previous study demonstrated that the HO-1 level in human osteoarthritis (OA) cartilages from type 2 diabetes mellitus (T2DM) after CoPP treatment was significantly lower than those from non-T2DM (Vaamonde-Garcia et al 2017 ). Given the contrasting effect of CoPP seen in HaCaT cultured in NG media versus those cultured in HG media, it was decided to investigated whether the difference in glucose concentration had any effect on the protein expressions of HO-1 and its upstream regulator, nuclear factor erythroid 2-related factor 2 (Nrf2) after CoPP treatment (Dong et al 2021 ). At the end of the migration assays, cells from each treatment group were collected and subjected to Western blotting analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated that the HO-1 level in human osteoarthritis (OA) cartilages from type 2 diabetes mellitus (T2DM) after CoPP treatment was significantly lower than those from non-T2DM (Vaamonde-Garcia et al 2017 ). Given the contrasting effect of CoPP seen in HaCaT cultured in NG media versus those cultured in HG media, it was decided to investigated whether the difference in glucose concentration had any effect on the protein expressions of HO-1 and its upstream regulator, nuclear factor erythroid 2-related factor 2 (Nrf2) after CoPP treatment (Dong et al 2021 ). At the end of the migration assays, cells from each treatment group were collected and subjected to Western blotting analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HaCaT cells were cultured in DMEM media added with 10%FBS. For the source of antibody and other reagent, refer to our published articles [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…HaCaT cells were seeded at a density of 2 × 10 4 cells in a 48-well plate for 24 h and then treated with compounds 1 – 4 (20–80 μM). The determination method of MTT assay is performed according to the previous paper [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous chemical investigations of Pleosporales sp. led to the isolation of heptaketides, chlamydosporols, diterpenoids, azaphilones, phenalenones, and other compounds. As a part of our ongoing study to discover novel bioactive metabolites from fungal endophytes, Pleosporales sp. YY-4 derived from the medicinal plant Uncaria rhynchophylla (Miq.)…”
mentioning
confidence: 99%